Ikonen der Nationen. Heldendarstellungen im post-sozialistischen Kroatien und Serbien - Sabo, Klaudija (De Gruyter, 2017)
The study examines how national myths in the former Yugoslavia were transformed in the 1990s, impacting the identity formation of ethnic groups and other collectives. Examining various visual media, it develops a comparative presentation of male and female heroic figures in Croatia and Serbia.